Return to Physical Activity After High Tibial Osteotomy or Unicompartmental Knee Arthroplasty: A Systematic Review and Pooling Data Analysis. Issue 5 (April 2021) - Belsey, James; Yasen, Sam K.; Jobson, Simon; Faulkner, James; Wilson, Adrian J.
Background: The 2 most common definitive surgical interventions currently performed for the treatment of medial osteoarthritis of the knee are medial opening wedge high tibial osteotomy (HTO) and medial unicompartmental knee arthroplasty (UKA). Research exists to suggest that physically active patients may be suitably indicated for either procedure despite HTO being historically indicated in active patients and UKA being more appropriate for sedentary individuals. Purpose: To help consolidate the current indications for both procedures regarding physical activity and to ensure that they are based on the best information presently available. Study Design: Systematic review. Methods: A search of the literature via the MEDLINE, Embase, and PubMed databases was conducted independently by 2 reviewers in accordance with the PRISMA (Preferred Reporting Items for Systematic Meta-Analyses) guidelines. Studies that reported patient physical activity levels with the Tegner activity score were eligible for inclusion. Patient demographics, operative variables, and patient-reported outcome scores were abstracted from the included studies. Results: Thirteen eligible studies were included, consisting of 401 knees that received HTO (399 patients) and 1622 that received UKA (1400 patients). The patients' mean age at surgery was 48.4 years for the HTO group and 60.6 years for the UKA group. Mean follow-up was 46.6 months (HTO) and 53.4 months (UKA). All outcome scores demonstrated an equal or improved score for activity and knee function regardless of the operation performed. Operative variables during HTO had a larger effect on outcome than during UKA. Conclusion: Patients who underwent HTO were more physically active pre- and postoperatively, but patients undergoing UKA experienced an overall greater increase in their physical activity levels and knee function according to Tegner and Lysholm scores. Activity after HTO may be influenced by operative factors such as the implant used and the decision to include a graft material in the osteotomy gap, although this requires further research. Some studies found that patients were able to return to physical activity postoperatively despite having an age or body mass index that would traditionally be a relative contraindication for HTO or UKA.